AI INTEGRATION IN VISUAL BRANDING STRATEGIES FOR LOCAL ARTISANS: THE BIORAMA APPROACH - Ramadhan, Gilang; Muhammad Eka Purbaya; Ratih Alifah Putri (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2025)
This study explores the use of artificial intelligence (AI) to enhance the digital branding of local organic artisans through the Design Thinking framework. The research is motivated by the persistent challenges faced by artisans in producing high-quality visual content, such as suboptimal lighting, simple composition, and limited variation, which hinder audience reach and digital appeal. By applying the Design Thinking stages of empathize, define, ideate, prototype, and test, this study collaborated with Biorama and three artisan partners to design and evaluate AI-based solutions, namely Gemini Veo 3 for promotional videos and ChatGPT for product photo enhancement. Testing conducted via the Instagram account @biorama___ in July 2025 revealed measurable improvements. Engagement rates ranged from 11.9% to 13.1%, with average likes between 41–59, comments 5–9, and reach between 499–651 per post. These findings confirm that AI interventions can deliver more appealing, realistic, and brand-aligned visual content for local artisans. The novelty of this research lies in the integration of prompt engineering into community-based digital branding practices, framed within the concept of creative placemaking. The study contributes theoretically to AI-driven branding strategies and offers practical guidance for artisans to strengthen their digital competitiveness.